2021
DOI: 10.1111/1471-0528.17013
|View full text |Cite
|
Sign up to set email alerts
|

Risk of preterm birth in relation to history of preterm birth: a population‐based registry study of 213 335 women in Norway

Abstract: Objective To assess the association between preterm first birth and preterm second birth according to gestational age and to determine the role of placental disorder in recurrent preterm birth.Design Population-based registry study.Setting Medical Birth Registry of Norway and Statistics Norway.Population Women (n = 213 335) who gave birth to their first and second singleton child during 1999-2014 (total n = 426 670 births).Methods Multivariate logistic regression analyses, adjusted for placental disorders, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
18
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
8
18
2
1
Order By: Relevance
“…History of a previous premature birth was one of the main risk factors for PTD. This finding is confirmed by previous studies (Sureshbabu et al, 2021) (Tingleff et al, 2022). Prelabour (premature) rupture of membranes (PROM) is a crucial risk factor for PTD and is responsible for about 30 percent of all preterm deliveries (Weissmann-Brenner et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…History of a previous premature birth was one of the main risk factors for PTD. This finding is confirmed by previous studies (Sureshbabu et al, 2021) (Tingleff et al, 2022). Prelabour (premature) rupture of membranes (PROM) is a crucial risk factor for PTD and is responsible for about 30 percent of all preterm deliveries (Weissmann-Brenner et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Studies have found that women with previous preterm deliveries had a higher risk of preterm birth in their next pregnancy. 20,24 However, in the stratified analyses, we observed no fertility treatment-associated increase in the risk of preterm birth among women with a history of preterm delivery. One explanation might be that women undergoing fertility treatment who have a history of preterm delivery might pay more attention to perinatal care, which could reduce the risk of preterm birth.…”
Section: Discussioncontrasting
confidence: 55%
“…6 Births between 34 and 37 weeks are called late preterm births. 7,8 This distinction is made at 34 weeks, when the health prognosis is significantly better than at earlier weeks. 8 In this study, the rate of preterm delivery of pregnant women with and without COVID-19 was compared based on 34 and 37 weeks of gestation.…”
Section: Protocolmentioning
confidence: 99%
“…7,8 This distinction is made at 34 weeks, when the health prognosis is significantly better than at earlier weeks. 8 In this study, the rate of preterm delivery of pregnant women with and without COVID-19 was compared based on 34 and 37 weeks of gestation. Premature birth rates determined according to 34 and 37 weeks of gestation were additionally compared between groups determined according to the trimester in which COVID-19 passed.…”
Section: Protocolmentioning
confidence: 99%